The Influence of the amount and impregnation sequence of potassium on the catalytic performance of Vox/Al2O3 for the non-oxidative dehydrogenation of n-butane - Volpe, María Alicia (2012)
The non-oxidative dehydrogenation of n-butane was studied over potassium-promoted supported vanadium alumina catalysts (at 823 K under atmosphere pressure) to explore the Influence of the amount and the order of potassium aggregation on the catalytic activity and selectivity towards olefins. The non-oxidative dehydrogenation activity and selectivity decreased with increasing K/V molar ratio. The best catalytic performance was obtained with 1 wt.% of potassium loading and when the promoter was first aggregated in the supported vanadium alumina catalysts. The order of promoter aggregation has effects in the catalytic activity. TPR (temperature programmed reduction) data indicate that less vanadium species are accessible to the reduction when low amount (1 wt.%) of alkali metal promoter was first introduced in these samples. After regeneration treatment, these promoted catalysts did not recover the full activity. Taking in account TPR results, this catalyst deactivation may be related to the irreversible structural transformation of surface vanadium oxide species by potassium.